Jahresring 38 : Der öffentliche Blick - König, Kasper; Obrist, Hans-Ulrich; Kulturkreis im Bundesverband der Deutschen Industrie e. V., Köln (München : Verlag Silke Schreiber, 1991)
Adams, Dennis, Armajani, Siah ; Bayrle, Thomas ; Bazile, Bernard ; Birnbaum, Dara ; Boetti, Alighiero ; Boltanski, Christian ; Bouabré, Frédéric Bruly ; Bruhin, Anton ; Büttner, Werner ; Butzmann, Manfred ; de Cordier, Thierry ; Corillon, Patrick ; Dumas, Marlene ; Durham, Jimmie ; Feldmann, Hans-Peter ; Fischli & Weiss ; Fritsch, Katharina ; Genzken, Isa ; Gerdes, Ludger ; Gette, Paul-Armand ; Graham, Dan ; Green, Renée ; Härtter, Bernhard ; Huang Yong Ping ; Huws, Bethan ; Kabakov, Ilya ; Koch, Udo ; Kroker, Arthur ; Lehanka, Marko ; Messager, Annette ; Miller, John, Müller, Chrstian Philip ; Paeffgen, C.O. ; Pettibon, Raymond ; Rehberger, Tobias ; Richter, Gerhard ; Roth, Dieter ; Samore, Sam ; Scher, Julia ; Schmit, Tomas ; Schnyder, Jean-Frédéric ; Schütte, Thomas ; Signer, Roman ; Virilio, Paul ; Wall, Jeff ; Weibel, Peter ; Weiner, Lawrence ; Wentworth, Richard ; Wool, Christopher ; Zobernig, Heimo
Duits & Engels
boek